The Role Of Syrian Seaports In The Reconstruction Stage (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research deals the role of the Syrian seaports (the ports of Latakia and Tartous) in the reconstruction process in Syria, as the research showed the role of Syrian maritime transport in the Syrian foreign trade and the work's indicators of Lattakia and Tartous ports and their navigation movement during the crisis period, and comparing it with the years before the crisis. The research discussed the digital indicators of Syrian seaports in the reconstruction stage and the extent of their ability to meet the requirements of this stage. The research also presented a number of recommendations that could contribute to raising the port's readiness for the reconstruction stage.